Enhancing employees’ workplace well-being through workplace digitization: exploring the mediating roles of job demands and digital anxiety - Han, Zhiyong; Song, Guoqing; Zhang, Yanlong; Yan, Lei (Frontiers in Psychology, 2025)
IntroductionWith the arrival of the digital era, workplaces are undergoing radical changes, and digitalization not only enhances work efficiency but also significantly influences employees’ workplace well-being. In this context, it is crucial for enterprises to actively promote digital transformation to gain a competitive edge. A significant challenge lies in liberating employees from monotonous tasks, thereby facilitating their engagement in more creative and analytical endeavors, which in turn enhances their workplace well-being. Consequently, investigating the mechanisms for improving workplace well-being during this transition has emerged as a critical area of inquiry in both scholarly and practical realms.MethodsBased on the Job Demands-Resources (JD-R) model, job demands and digital anxiety are introduced as mediating variables, and a dual-mediation model is constructed to explore the specific mechanism through which workplace digitization affects workplace well-being. A three-stage follow-up survey was conducted, resulting in 382 valid samples for rigorous statistical analysis.ResultsThe results show that workplace digitization positively impacts workplace well-being. Job demands and digital anxiety mediate the association between workplace digitization and workplace well-being. Additionally, workplace digitization reduces job demands and digital anxiety, which in turn enhances employees’ workplace well-being. These findings provide theoretical guidance on how management practices can enhance employees’ workplace well-being.DiscussionBased on the JD-R model, this study expands the research scope of workplace digitization outcome variables and enriches the antecedents of workplace well-being. By applying the JD-R model, this research positions workplace digitization as a macro-level organizational intervention that influences workplace well-being through both loss and gain pathways, thereby contributing valuable insights into its antecedents.